ANALISIS PENGELOLAAN MODAL KERJA PADA KOPERASI PERKEBUNAN SAKO JATI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Citra Suwarno; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the management of working capital of Koperasi Perkebunan Sako Jati Kecamatan Pangean Kabupaten Kuantan Singingi in the 2014-2018 period measured using financial ratio standards. Types and sources of data used in this study are secondary data, namely data obtained from cooperatives, including cooperative financial report data and other data related to research materials. From the results of the data analysis research (1) Analysis of activity ratio with indicators of Total AssetTurnover, Working Capital Turnover, Cash Turnoverand Receivable Turnoverfluctuated and accounts receivable turnover was still very low. (2) Analysis of the Liquidity Ratio with Current Ratio and Cash Ratio indicators are in bad categories and tend to fluctuate. And (3) Analysis of Profitability Ratios with indicators of Profit Margin, Return on Assets and Return on Equity shows an increase in the ratio used during the last five years.Keywords: Working Capital, Activity, Liquidity, Profitability